2019
DOI: 10.1016/j.ajhg.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Prevalence and Health Consequences of Uniparental Disomy in Four Million Individuals from the General Population

Abstract: Meiotic nondisjunction and resulting aneuploidy can lead to severe health consequences in humans. Aneuploidy rescue can restore euploidy but may result in uniparental disomy (UPD), the inheritance of both homologs of a chromosome from one parent with no representative copy from the other. Current understanding of UPD is limited to $3,300 case subjects for which UPD was associated with clinical presentation due to imprinting disorders or recessive diseases. Thus, the prevalence of UPD and its phenotypic consequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 44 publications
(86 reference statements)
2
103
4
3
Order By: Relevance
“…A recent study of the prevalence of UPD, using computational detection of DNA segments that were identical by descent and runs of homozygosity, estimated the incidence to be approximately 1 in 2,000 births. This was nearly twice the frequency previously thought [6]. A consequence of UPiD is that it allows two copies of a recessive mutation to be transmitted from a heterozygous carrier parent to the child in whom the mutation will be present in the homozygous state [5].…”
Section: Discussionmentioning
confidence: 96%
“…A recent study of the prevalence of UPD, using computational detection of DNA segments that were identical by descent and runs of homozygosity, estimated the incidence to be approximately 1 in 2,000 births. This was nearly twice the frequency previously thought [6]. A consequence of UPiD is that it allows two copies of a recessive mutation to be transmitted from a heterozygous carrier parent to the child in whom the mutation will be present in the homozygous state [5].…”
Section: Discussionmentioning
confidence: 96%
“…Risk of AR conditions, such as CHS, are easily estimated with siblings having a 25% risk of developing the disease. However, the prevalence of germline UPD is harder to quantify with frequencies from 0.03 -0.3% (37)(38)(39)(40), being partial-UPiD s i g n ifi c a n t ly l ow er ( 4 0 ) . D e s p i te th e l o w r i s k o f recurrence, having detected the heterozygosis c.8380dupT variant in the mother of this child and defined the inheritance mechanism, will allow a more accurate genetic counseling for future pregnancies and other family members at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the counselling of the affected individual's family has to be adjusted accordingly: in contrast to usual autosomal recessive inheritance in MPS I with a typical reoccurrence risk for further affected children of 25%, the reoccurrence risk for a uniparental isodisomy affecting the telomeric end of chromosome 4 is diminishingly small. In general, the estimated incidence for UPD – at least with a clinical manifestation – used to be low; the occurrence of longer stretches of isodisomy is even less common [ 16 , 20 ]. Naturally, risk factors like age of the mother, the possibility of more complex chromosomal arrangements in the parents and the genetic base line risk of 2–5% have to be taken into consideration [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, larger cross-sectional studies revealed that UPD in the general “healthy” population might be much higher than estimated, often without the prevalence of symptoms; i.e. “hidden” partial / segmental isodisomy (isoUPD) with a frequency of 0.578% in healthy individuals (currently 3.650 cases documented [ 16 , 20 , 24 ]) . Interestingly, it was also shown that mosaic partial UPD (i.e.…”
Section: Discussionmentioning
confidence: 99%